2015
DOI: 10.1088/1009-0630/17/4/14
|View full text |Cite
|
Sign up to set email alerts
|

The Calibration of the DD Neutron Indium Activation Diagnostic

Abstract: The indium activation diagnostic was calibrated on an accelerator neutron source in order to diagnose deuterium-deuterium (DD) neutron yields of implosion experiments on Shenguang-III facility. The scattered neutron background of the accelerator room was measured by placing a polypropylene shield in front of indium sample, in order to correct the calibrated factor of this activation diagnostic. The proper size of this shield was given by Monte Carlo simulation software. The affect from some other activated nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, our preliminary design analysis showed that neutron yield is not high enough to produce acceptable signal-to-noise ratio on our current laser facilities. The neutron yield was measured by a scintillator detector and Indium activation diagnostic [27,28]. The ion temperature was measured by a nToF detector with an accuracy of 15% [29].…”
Section: Methodsmentioning
confidence: 99%
“…However, our preliminary design analysis showed that neutron yield is not high enough to produce acceptable signal-to-noise ratio on our current laser facilities. The neutron yield was measured by a scintillator detector and Indium activation diagnostic [27,28]. The ion temperature was measured by a nToF detector with an accuracy of 15% [29].…”
Section: Methodsmentioning
confidence: 99%
“…Indium has been used routinely in the past at both OMEGA-60 and the NIF. Today it is used for dd-neutron yield measurements at the Z-facility [100] and Shenguang-II facility [106,107].…”
Section: Neutron Activation Diagnosticsmentioning
confidence: 99%